Comparison of early and late percutaneous tracheotomies in adult intensive care unit - Duran,Mehmet (2014)
Background and objectives: Percutaneous tracheotomy has become a good alternative for patients thought to have prolonged intubation in intensive care units. The most important benefits of tracheotomy are early discharge of the patient from the intensive care unit and shortening of the time spent in the hospital. Prolonged endotracheal intubation has complications such as laryngeal damage, vocal cord paralysis, glottic and subglottic stenosis, infection and tracheal damage. The objective of our study was to evaluate potential advantages of early percutaneous tracheotomy over late percutaneous tracheotomy in intensive care unit. Methods: Percutaneous tracheotomies applied to 158 patients in adult intensive care unit have been analyzed retrospectively. Patients were divided into two groups as early and late tracheotomy according to their endotracheal intubation time before percutaneous tracheotomy. Tracheotomies at the 0–7th days of endotracheal intubation were grouped as early and after the 7th day of endotracheal intubation as late tracheotomies. Patients having infection at the site of tracheotomy, patients with difficult or potential difficult intubation, those under 18 years old, patients with positive end-expiratory pressure above 10 cmH2O and those with bleeding diathesis or platelet count under 50,000 dL−1 were not included in the study. Durations of mechanical ventilation and intensive care stay were noted. Results: There was no statistical difference among the demographic data of the patients. Mechanical ventilation time and time spent in intensive care unit in the group with early tracheotomy was shorter and the difference was statistically significant (p < 0.05). Conclusion: Early tracheotomy shortens mechanical ventilation duration and intensive care unit stay. For that reason we suggest early tracheotomy in patients thought to have prolonged intubation.